Peningkatan Hasil Belajar Peserta Didik Melalui Penerapan Model Project Based Learning (PBL) dengan Pendekatan Teaching at The Right Level (TaRL) Pada Materi Menulis Teks Deskripsi Siswa Kelas 5 SD - Herdiana, Berta; Hizriyani, Rina; Fauziah, Nita (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to evaluate the effectiveness of implementing Project Based Learning (PBL) and Teaching at the Right Level (TaRL) in enhancing the descriptive writing skills of 5th-grade students. The research utilized a qualitative approach with observation, interviews, and analysis of students' written works. The data obtained will be analyzed using a thematic approach to identify emerging patterns regarding the impact of the use of PBL and TaRL on students' ability to write descriptive texts. The results show that both PBL and TaRL significantly improve student motivation and writing skills. PBL increased student engagement by involving them in real-life projects, making the learning process more relevant and meaningful. Meanwhile, TaRL tailored instruction to students' individual learning levels, allowing them to progress at their own pace and enhancing their confidence. The findings suggest that combining both approaches provides an inclusive and effective strategy for improving students' descriptive writing skills in elementary education